Hepatic steatosis and PNPLA3 I148M variant are associated with serum Fetuin‐A independently of insulin resistance. (July 2014) - Rametta, Raffaela; Ruscica, Massimiliano; Dongiovanni, Paola; Macchi, Chiara; Fracanzani, Anna L.; Steffani, Liliana; Fargion, Silvia; Magni, Paolo; Valenti, Luca
Abstract Background & Aims Fetuin‐A is a liver‐derived peptide associated with insulin resistance. Aim of this cross‐sectional study was to evaluate whether Fetuin‐A is increased in patients with nonalcoholic fatty liver disease (NAFLD) vs. healthy subjects without metabolic abnormalities and the association with insulin resistance and liver damage. To investigate the causal relationship between fatty liver and Fetuin‐A, we also analysed whether the inherited I148M PNPLA3 variant modulates Fetuin‐A. Methods In 137 patients with histological NAFLD, complete metabolic characterization, PNPLA3 genotype, and in 260 healthy subjects without metabolic alterations, Fetuin‐A was measured by enzyme‐linked immunoabsorbent assay. Results Serum Fetuin‐A was higher in NAFLD patients than in controls (P < 0·0001), independently of age, sex, BMI, insulin resistance, dyslipidemia, adiponectin, PNPLA3 I148M and ALT levels (OR 1·006 95% CI 1·003–1·11; P = 0·003). In NAFLD patients, Fetuin‐A was associated with steatosis severity (P = 0·03) and metabolic syndrome features, but not with hepatic inflammation. At multivariate analysis, Fetuin‐A levels were associated with BMI, triglycerides, hyperglycemia and PNPLA3 I148M (P = 0·034) independently also of age, sex and ALT levels. As PNPLA3 I148M is a strong and inherited determinant of liver fat without affecting insulin resistance and lipid levels, these data suggest that steatosis has a causal role in determining serum Fetuin‐A levels. Conclusions Liver fat accumulation and the I148M variant of PNPLA3 are associated with serum Fetuin‐A levels independently of insulin resistance. Fetuin‐A may be implicated in the pathogenesis of metabolic complications associated with NAFLD.